2016
DOI: 10.1021/acs.analchem.6b01476
|View full text |Cite
|
Sign up to set email alerts
|

Protein Pretreatment of Microelectrodes Enables in Vivo Electrochemical Measurements with Easy Precalibration and Interference-Free from Proteins

Abstract: In vivo electrochemistry is one powerful strategy for probing brain chemistry. However, the decreases in sensitivity mainly caused by the adsorption of proteins onto electrode surface in short-term in vivo measurements unfortunately render great challenges in both electrode calibration and selectivity against the alternation of proteins. In this study, we observe that the pretreatment of carbon fiber microelectrodes (CFEs) with bovine serum albumin (BSA) would offer a simple but effective strategy to the chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 59 publications
(119 reference statements)
5
62
0
Order By: Relevance
“…It is imperative that the sensor demonstrates efficient stability for continuous long term recordings. The potential benefits of pre-treating microelectrodes with lipids [29,38] and proteins [39] has been investigated by research groups to permit more accurate pre-calibration techniques by mitigating this sensitivity decrease observed upon implantation. These studies have established that exposing the electrodes to fouling agents in vitro may serve as a good model of the behaviour of implanted sensors in brain tissue.…”
Section: Resultsmentioning
confidence: 99%
“…It is imperative that the sensor demonstrates efficient stability for continuous long term recordings. The potential benefits of pre-treating microelectrodes with lipids [29,38] and proteins [39] has been investigated by research groups to permit more accurate pre-calibration techniques by mitigating this sensitivity decrease observed upon implantation. These studies have established that exposing the electrodes to fouling agents in vitro may serve as a good model of the behaviour of implanted sensors in brain tissue.…”
Section: Resultsmentioning
confidence: 99%
“…3 The enhanced electrochemical properties of CNTYMEs are attributed to the alignment of the CNTs, which exposes the ends of the tubes that contain more oxygen functional groups known to promote adsorption of neurotransmitters such as dopamine. 48 Moreover, the ability to fabricate CNT yarns directly into electrodes in a manner similar to CFMEs dramatically simplifies the electrode fabrication process and improves the reproducibility. 9,10 One main advantage of CNTYMEs is that the dopamine signal is independent of the repetition rate of the applied voltage waveform for FSCV, a stark contrast to traditional CFMEs which dramatically lose sensitivity with increasing repetition rate.…”
Section: Introductionmentioning
confidence: 99%
“…These results demonstrate that the coating of PEDOT‐PC membrane does not affect the electrode sensitivity toward DA. This is a step forward from electrode coatings with conventional antifouling membranes or BSA that compromise current responses of DA . Furthermore, the current recorded at the PEDOT‐PC/CFE was stable compared to that at bare CFE (Figure C and the Supporting Information, Figure S5), suggesting that PEDOT did not adsorb the product of DA oxidation, which was frequently observed at carbon electrodes…”
Section: Methodsmentioning
confidence: 96%
“…Towards the goal of minimizing the protein adsorption on the brain‐implanted microelectrodes, we previously found that pre‐treatment of CFEs with bovine serum albumin (BSA) can minimize further adsorption of proteins when the electrodes are implanted into the rat brain; however, this also causes significant sensitivity drop of CFEs to neurochemicals, including DA …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation